Glucose intolerance in the third trimester is not predictive of adverse outcomes. Issue 1 (29th July 2019) - Fonseca, Andreia; Lopes, João; Clode, Nuno
Abstract: Objective: To evaluate the incidence of abnormal third trimester oral glucose tolerance tests (OGTT) results in non‐diabetic women and to compare the obstetric and neonatal outcomes with those of women with normal OGTT results. Methods: Women with third trimester singleton pregnancies with negative gestational diabetes test results earlier in their pregnancy were enrolled into an observational prospective study at a tertiary care hospital between June 1, 2014 and September 30, 2017. All underwent an additional 75 g OGTT between 32 and 36 weeks and were classified as having normal or abnormal results. Healthcare professionals were blinded to the results. Pregnancy and perinatal outcomes were compared. Results: Four hundred and sixty‐seven women agreed to participate and 334 fulfilled the inclusion criteria. Forty‐five (13.5%) had an abnormal third trimester OGTT result. In this group, post‐term induction of labor was more frequent (70.6% vs 38.1%, adjusted odds ratio (aOR) 4.28, 95% confidence interval (CI) 1.33–13.77, P =0.015) as was cesarean delivery (31.1% vs 15.2%, aOR 2.57, 95% CI 1.14–5.81, P =0.023), regardless of surgery indication. Macrosomia was more common, but not significantly after adjusting for confounders (17.8% vs 4.2%, aOR 3.80, 95% CI 0.60–24.17, P =0.157). No other significant differences were found. Conclusion: Post‐term induction of labor and cesarean delivery were more frequent in women with an abnormal third trimester OGTT result, but there was no increased risk of serious maternal or perinatal adverse outcomes. Abstract : Women with abnormal third trimester oral glucose tolerance test results do not have increased risk of serious maternal or perinatal adverse outcomes.